Maximizing the Implementation Quality of Evidence-Based Preventive Interventions in Schools: A Conceptual Framework - Domitrovich, Celene E. (Adv Sch Ment Health Promot, 2008)
Increased availability of research-supported, school-based prevention programs, coupled with the growing national policy emphasis on use of evidence-based practices, has contributed to a shift in research priorities from efficacy to implementation and dissemination. A critical issue in moving research to practice is ensuring high-quality implementation of both the intervention model and the support system for sustaining it. The paper describes a three-level framework for considering the implementation quality of school-based interventions. Future directions for research on implementation are discussed.